Cervical Sagittal Alignment in Extensive Fusions for Lenke 3C and 6C Scoliosis: The Effect of Upper Instrumented Vertebra. Issue 6 (15th March 2017) - Yanik, Hakan Serhat; Ketenci, Ismail Emre; Erdem, Sevki
Abstract : Study Design: A retrospective analysis of cervical sagittal alignment (CSA) in Lenke 3C and 6C adolescent idiopathic scoliosis (AIS). Objective: The aim of this study was to evaluate CSA according to upper instrumented vertebra (UIV) level. Summary of Background Data: Hypokyphotic effect of extensive fusions of Lenke 3C and 6C curves on thoracic spine leads to kyphotic changes in cervical region. No study has evaluated the CSA in these patients according to UIV level. Methods: A total of 55 Lenke 3C and 6C AIS patients who underwent posterior fusion with pedicle screw instrumentation were recruited in this study. Patients were divided into three groups according to UIV level, which was determined preoperatively on the basis of shoulder balance. There were 22, 19, and 14 patients in T2, T3, and T4 groups, respectively. Three groups were similar according to demographic and preoperative coronal and sagittal alignment parameters. Patients were compared at two-year follow-up according to radiographic changes in coronal and sagittal planes. Main sagittal parameters were C2-C7 cervical lordosis (CL), T1 slope, T1-T5, and T5-T12 kyphosis. Clinical outcomes were assessed using scoliosis research society (SRS)-22 and short form (SF)-36 questionnaires. Results: In all patients, C2-C7 CL, T5-T12 kyphosis, and T1 slope significantly decreased postoperatively ( P  < 0.05). The amount of decrease was similar between groups. T1-T5 kyphosis did not change significantly in all groups. Twenty-seven patients had postoperative cervical kyphosis (CK). Thirteen of them had preoperative CL and 14 had CK. Twenty-eight of 41 patients with preoperative CL remained in lordotic CSA postoperatively. SRS-22 and SF-36 scores did not change significantly after the surgery. Conclusion: In Lenke 3C and 6C AIS, postoperative CSA is independent from UIV level. Decreased CL is mainly caused by T5-T12 and T1 slope decrease. In order to achieve level shoulders, fusion can be extended to appropriate upper level, without increased risk of CK. Level of Evidence: 4